Moving beyond disciplinary silos: The potential for transdisciplinary research in Sport for Development - Whitley, Meredith A; Collison-Randall, Holly; Wright, Paul M; Darnell, Simon C; Schulenkorf, Nico; Knee, Eric; Holt, Nicholas L; Richards, Justin (Journal of sport for development, 2022)
The Sport for Development (SfD) field is transdisciplinary by nature, and yet scholars tend to stay within their disciplinary perspectives in their study of SfD. There is a need for more collaborative and collective approaches in SfD research. Transdisciplinary research facilitates conceptual, theoretical, philosophical, and methodological innovations that transcend disciplinary boundaries, creating new knowledge that can advance a field. The purpose of this paper is to critically review the disciplinary trends in SfD research within (respectively) sport sociology, social anthropology, sport management, public health, leisure, sport pedagogy, and sport psychology, with a particular focus on where there may be intersection, duplication, obfuscation, and omission between these disciplines. Disciplinary intersections are then considered, along with gaps in the SfD evidence base that are ripe for transdisciplinary research. The paper concludes with an exploration of possibilities for future transdisciplinary research in SfD.